A SOIOLINGUISTICS ANALYSIS OF WOMEN’S LANGUAGE FEATURES AND FUNCTIONS IN THE FILM ELEMETAL - Arya, I Gusti Ayu Dyanka Namira Putri; Dewa Ayu Kadek, Claria; Swari, Radha Andhra (ENGLISH, 2026)
This study examines the features and functions of women's language used by female characters in the film Elemental. The research is based on Lakoff’s (2004) framework on women's language features and Pearson’s (1985) theory on language functions. Using documentation and note-taking methods, the research analyzes the frequency of women’s language features in the characters’ speech. The analysis identified eight features of women’s language: lexical hedges or fillers, empty adjectives, intensifiers, hypercorrect grammar, super-polite forms, avoidance of strong swear words, rising intonation, and emphatic stress, with lexical hedges or fillers appearing most frequently. Four language functions were also found. The lexical hedges helped initiate discussions and express feelings, while intensifiers, emphatic stress, and empty adjectives conveyed emotions. Hypercorrect grammar, super polite forms, and avoiding strong swear words functioned to soften speech. These findings indicate that women’s language in Elemental is predominantly used for emotional expression and interaction politeness, suggesting that the film constructs its female characters through linguistic patterns traditionally associated with feminity. This representation reflects how media discourse can reproduce conventional gendered communication norms, positioning women as emotionally expressive and socially attentive speakers, and thus contributes to broader discussion about how popular media shapes and reinforces gender representation through language.